Equine Herpes Virus-1. A clinician’s perspective. - Tyrnenopoulou, P; Diakakis, N (Journal of the Hellenic Veterinary Medical Society, 2023)
Equid herpesvirus type 1 (EHV-1) is a common pathogen of horses with worldwide distribution. In light of recent outbreaks reported across Europe and United States of America, the contagious nature of this disease is highlighted and re-evaluation of diagnostic procedures, treatment modalities and biosecurity protocols is imperative. This review provides an overview of the epidemiology, current treatment protocols and prognosis for EHV-1-associated syndromes, with an emphasis on the neuropathogenic strain of EHV-1.